KOMPOSISI NUTRIEN DAN PERTUMBUHAN MIKROALGAE Chaetoceros gracilis YANG DIKULTURKAN PADA BERBAGAI KONSENTRASI KARBONDIOKSIDA - Khairuddin, Khairuddin; Sahabuddin, Sahabuddin (Journal Galung Tropika, 2012)
This research aimed at observing the influence of the additional carbondioxide concentrations in cultured media to quantity and quality of microalgae Chaetoceros gracilis.The research container was a polyethylene line of 50 l volume which initial stocking density 105 cel/mlof C.gracilis and polycarbonate tank 100 l volume for tiger shrimp larvae rearing with stocking density of 100 naupli /l. The carbondioxide used were commercial carbondioxide injected in aeration system ofC. gracilis culture media. The experiments tried with different carbondioxide concentrations were, A = 0% (Non additional CO2), B = 2%, C = 4% and D = 6% with three repetition times. The result of the research revealed that experiment of the additional carbondioxide in culture media increasing protein and BETN,but decreasing of fat, ash and crude fibre C.gracilis. The best carbondioxide concentrations to growth rate C. gracilis obtained in 2% (v/v) carbondioxide concentrations.